In Vitro Human Dihydroorotate Dehydrogenase Inhibitory, Anti-inflammatory and Cytotoxic Activities of Alkaloids from the Seeds of Nigella glandulifera - Gao, Jun-Bo; Zhang, Xing-Jie; Zhang, Rui-Han; Zhu, Li-Li; Pu, De-Bing; Li, Xiao-Li; Li, Hong-Lin; Xu, Min; Xiao, Wei-Lie (Planta Medica, 2018)
Four new dolabellane-type diterpene alkaloids, glandulamines A – D (1 – 4), together with twelve known compounds (5 – 16), were isolated from the seeds of Nigella glandulifera using repeated column chromatography and semipreparative HPLC. The structures of 1 – 16 were elucidated based on NMR data analysis, HRMS experiments and other spectroscopic interpretations. The absolute configuration of 5 was determined by single-crystal X-ray diffraction data for the first time. Compounds 10 and 12 showed human dihydroorotate dehydrogenase inhibitory activity with IC50 values of 61.1 ± 5.3 and 45.9 ± 3.0 µM, respectively. Molecular docking of the active compound 12 and positive control teriflunomide on the inhibitor-binding site of human dihydroorotate dehydrogenase was subsequently performed to visualize the interaction pattern. In addition, compounds 8 and 10 exhibited inhibitory effects against lipopolysaccharide-induced nitric oxide production with inhibition rates of 61 and 41%, respectively, at the concentration of 10 µM. Compounds 9 and 12 showed cytotoxic activities with cell viability varying from 29 ~ 57% at 100 µM against T98G, U87, U251, and GL261 glioma cancer cell lines. These data provide new insights on the pharmacologically active compounds of this plant widely used in folk medicine.
Keywords: dolabellane-type diterpene alkaloids; Ranunculaceae; Nigella glandulifera; human dihydroorotate dehydrogenase; lipopolysaccharide; nitric oxide production; cytotoxic activity